Well-Being of Caregivers of Patients with Laryngeal Cancer Treated by Radiotherapy - Karlsson, Therese; Johansson, Mia; Finizia, Caterina (International Archives of Otorhinolaryngology, 2020)
Introduction Laryngeal cancer is the second most common head and neck cancer, but no study to date reports exclusively on the well-being of the caregivers of patients with laryngeal cancer treated by radiotherapy.Objective The present prospective pilot study aims to describe the impact of the work on the well-being of the caregivers of patients with laryngeal cancer.Methods The caregivers of patients undergoing radiotherapy with curative intent for laryngeal cancer were included in the present study, and they were asked to fill out a specific questionnaire, while the patients filled out the Hospital Anxiety and Depression Scale (HADS) following diagnosis but prior to treatment.Results A total of 50 caregivers were included, 20% of which were male, and 80%, female. In total, 62% (n = 31) of the caregivers were spouses, while the remaining were daughters/sons (n = 11; 22%), siblings (n = 6; 12%), or they were classified as “other” (n = 2; 4%). The female caregivers scored lower (worse) on the depression/worry domain, and this was statistically significant (p = 0.047); they also reported a statistically significant higher negative impact on employment (p = 0.011) compared with the male caregivers. In general, the caregivers of patients with late-stage tumors tended to report lower (worse) scores on all domains (except hospital contact) compared with the caregivers of patients with early-stage tumors. No other differences were observed regarding the patients' age, gender, tumor site or their HADS score.Conclusion The diagnosis and treatment of laryngeal cancer impacts the caregiver's psychological well-being, particularly that of female caregivers. This should be taken into consideration when the patients begin the hospital treatment pathway. However, larger studies are needed to target resources more appropriately.
Keywords: laryngeal cancer; quality of life; radiotherapy/caregivers